2019
DOI: 10.4102/phcfm.v11i1.2046
|View full text |Cite
|
Sign up to set email alerts
|

Stress and resilience among women living with HIV in Nigeria

Abstract: BackgroundPsychological morbidities concurrent with HIV have been the focus of considerable scientific investigations. However, researchers have largely overlooked HIV-related stress and resilience among women living with HIV in rural communities.AimThis study explored the associations between psychological resilience and HIV-related stress among women living with HIV.SettingThe study was conducted in three randomly selected hospitals that provide primary HIV care in Niger state, Nigeria.MethodsA predictive cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
4
17
0
1
Order By: Relevance
“…The participants did not present themselves as victims of the infection, they presented themselves as independent individuals whom, with the support of their relatives, friends, church leaders, worshippers, TASO and health care providers, were able to gain a greater quality of life and recognition in the community. Similar findings were reported in other studies [19,40,41,42]. Hence, the discovery of the HIV infection that had initially created a negative impact on the lives of the participants, seemed to have been a driving force on the empowering changes during the years.…”
Section: Discussionsupporting
confidence: 88%
“…The participants did not present themselves as victims of the infection, they presented themselves as independent individuals whom, with the support of their relatives, friends, church leaders, worshippers, TASO and health care providers, were able to gain a greater quality of life and recognition in the community. Similar findings were reported in other studies [19,40,41,42]. Hence, the discovery of the HIV infection that had initially created a negative impact on the lives of the participants, seemed to have been a driving force on the empowering changes during the years.…”
Section: Discussionsupporting
confidence: 88%
“…Stigma has been established in several studies as the main driver of the HIV epidemic as well as a major barrier to the HIV care cascade [42,[46][47][48]. This is further complicated by "ageism" especially among older adults living with HIV [49].…”
Section: Hiv-related Stigmamentioning
confidence: 99%
“…Similarly, fear of stigma and non-disclosure of HIV status could affect older PLWH willingness to access social support [46,72]. Studies have shown that supportive environment and social relationships can build self-esteem and self-efficacy of older adults living with HIV [46,47]. Also, research from SSA has shown that access to HIV services and social support impacted the overall wellbeing of PLWH [10,47].…”
Section: Isolation Of Older Adults In Global Response To Hiv: a "Brewing Epidemic"mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in the literature with respect to stress among Nigerian women is limited as existing research has focused mainly on occupational settings [17][18][19]. However, Adamu et al reported moderate levels of perceived stress among HIV positive women [20].…”
Section: Introductionmentioning
confidence: 99%